ENERGY TRANSITION IN ASEAN–6: EMPIRICAL EVIDENCE ON THE IMPACT OF ECONOMIC GROWTH, CARBON EMISSIONS, AND FOREIGN INVESTMENT - Rhani, Nanda Muthiah; Azwardi, Azwardi Muthiah; Bashir, Abdul Muthiah (Universitas KH. Abdul Chalim Mojokerto, 2026)
This study analyzes the influence of economic growth, carbon emissions, and Foreign Direct Investment (FDI) on renewable energy consumption in Indonesia, Singapore, Malaysia, Vietnam, the Philippines, and Thailand. The data used is panel data, with the selected model being the Fixed Effect Model (FEM). The results show that economic growth and FDI play a role in driving increased renewable energy consumption, while carbon emissions remain a challenge in the transition to green energy. Overall, economic dynamics, the environment, and foreign investment are closely linked in determining the direction of renewable energy development in this region. Therefore, policies that support investment in green energy, strengthening environmental regulations, and developing renewable energy infrastructure are needed to ensure future energy sustainability.